Incidencia de la cartera vencida en el patrimonio de la cooperativa de ahorro y crédito Cacpeco del cantón Latacunga, provincia Cotopaxi en el primer semestre del 2016 - Sangacha Guamán, Janina Katherine (2017)
CACPECO Ltda., The Cotopaxi Small Business Savings and Credit Cooperative, Is located in Latacunga city, IT Is regulated by the Popular and Solidarity Economy Superintendency [SEPS] And controlled by the Monetary and Financial Regulation Board [JRMF], the money raising and placement is as main activity, it Is recorded according to its assets balance in segment 1. It has a specific accounting structure where its main asset is the loan portfolio with 62.58% of the total assets until June. In the last years, Ecuador has presented an economic slowdown which causes the delinquency rate increase by 1.5% in the cooperative system according to SEPS data. So that, this research determines the incidence that it has the portfolio overdue in relation to equity in the 2016 first half. The descriptive and documentary methodologies were applied in it, allowing the necessary figures collection that were used in the several financial ratios application, between these assets quality, profitability and solvency. The analysis results show that CACPECO reflects a good stability against the relation portfolio overdue-equity. This is especially evident in the solvency indices with a slight exposure of the equity in reference to portfolio overdue, so that a considerable equity support with credit card portfolio. This result is strengthened for the other indices which demonstrate adequate credit placement and recovery. It is important to point that starting from June the cooperative adopted and reinforced its policies and proper strategies due to country economic reality, evidencing in the financial indicators percentages shown in the last month.